Functionalized Selenium Nanoparticles Synergizes With Metformin to Treat Breast Cancer Cells Through Regulation of Selenoproteins - Yang, Yu; Zhang, Zehang; Chen, Qi; You, Yuanyuan; Li, Xiaoling; Chen, Tianfeng (Frontiers in Bioengineering and Biotechnology, 2021)
Owing to high blood sugar level and chronic inflammation, diabetes tend to cause the overproduction of free radicals in body, which will damage tissue and cells, reduce autoimmunity, and greatly increase the incidence of tumors. Selenium nanoparticles (SeNPs) exhibit high antioxidant activity with anti-tumor ability. In addition, metformin is considered as a clinical drug commonly for the treatment of stage II diabetes. Therefore, in this study, different functionalized SeNPs combined with metformin were performed to detect the feasibility for cancer therapy. The combination of Tween 80 (TW80)-SeNPs and metformin was found to have a synergistic effect on MCF-7 cells. The mechanism of this synergistic effect involved in the induction of DNA damage by affecting the generation of reactive oxygen species through selenoproteins; the upregulation of DNA-damage-related proteins including p-ATM, p-ATR, and p38; the promotion of p21 expression; and the downregulation of cyclin-dependent kinases and cyclin-related proteins causing cell cycle arrest. Furthermore, the expression of AMPK was affected, which in turn to regulate the mitochondrial membrane potential to achieve the synergistic treatment effect.